(14/6x)-(3/6x)=100

Simple and best practice solution for (14/6x)-(3/6x)=100 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (14/6x)-(3/6x)=100 equation:


x in (-oo:+oo)

(14/6)*x-((3/6)*x) = 100 // - 100

(14/6)*x-((3/6)*x)-100 = 0

(14/6)*x+(-1/2)*x-100 = 0

11/6*x-100 = 0 // + 100

11/6*x = 100 // : 11/6

x = 100/11/6

x = 600/11

x = 600/11

See similar equations:

| 2m+3w=104 | | 20x+15y=2600 | | 24x+2x+5=17 | | (14/6)x-(3/6)x=100 | | -20/1x6/5 | | 6x+4=3-(9x-8) | | 6x+14=16x-6 | | (my-5x)/3z=5y | | 8x-4x=72+16 | | logx=169 | | my-5x=5y(3z) | | 5=(-z+3) | | 4x^2+9y^2-16x+18y=11 | | 2x+x=25+2 | | 2x^2-8x+10=x^2+2x-6 | | 6m+8=2m+32 | | x^3-2x^2-5x-6= | | (7n-6)(n+7)=0 | | .948=.75x-ln(x) | | 20=67-f | | .948=.75x-lnx | | (3x-16)=x | | 13q-11q-q=12 | | 10+3(4x-2)=-32 | | 10+44=10k-10 | | 8x+5x-15=9x-6x-1 | | 6x(x-2)= | | 2+2(5x-4)=7-5(2x+1) | | Y/3=96 | | 3n^2+24=22n | | 3.4/3 | | 3x+3[5x-7x]=12-x |

Equations solver categories